The Effect of Profitability Ratios on Financial Distress in Islamic Commercial Banks in Indonesia - yennita sari; nofinawati nofinawati; sarmiana batubara; ferri alfadri (Institut Agama Islam Negeri Padangsidimpuan, 2020)
ROA and ROE affect the Financial Distress that is if the percentage value of ROA and ROE is at a high value, it can be said that the company is still far from financial distress. The higher the return on assets means the higher the amount of net profit generated and vice versa. ROA and ROE which have increased and financial distress have increased occurred in Muamalat Indonesia bank in 2016, Bank Rakyat Indonesia in 2016, Bank Negara Indonesia in 2016 and 2018, Bank Central Asia in 2017, Bank Syariah Mandiri in 2016, Bank Panin Syariah in 2017 , Bank Mega Syariah in 2015, Bank Bukopin Syariah in 2016, Bank Victoria Syariah in 2018, Maybank Syariah in 2017, Bank Syariah State Pensioners in 2015 and 2018 and the value of Return on Assets which declined and the value of financial distress also decreased in banks. Mega Syariah in 2018, Bank Victoria Syariah in 2018, Bank Panin Syariah in 2015, and Bank Bukopin Syariah in 2018. Formulation of the problem in this study is whether there is an influence of ROA and ROE on financial distress in Islamic commercial banks in Indonesia in 2014-2018 . The purpose of this study was to determine the effect of ROA and ROE on financial distress in Islamic commercial banks in Indonesia in 2014-2018. The discussion of this study deals with the analysis of financial statements and profitability ratios and financial distress by using the Zmijewski X-score method. This research is a quantitative study using panel data regression analysis. The data used are time series data for 2014-2018 published through the official website of each Islamic commercial bank in Indonesia, which was analyzed using Software Eviews 9. Partial ROA has a tcount value Ftable (4.664855 2.77) which means that both variables affect the financial distress variable in 2014-2018. Based on the results of the acquisition R2 of 0.592051, it means that 59 percent of financial distress is influenced by ROA and ROE while 41 percent is influenced by other variables not discussed in this study.